Heat Exchanger Versus Storage Tank for Hot Tap Water Preparation in District Heating Systems. (2016) - Manescu, Radu
Abstract: Buildings energy consumption accounts for almost a half of the world energy consumption representing one third of the annual greenhouse gas emissions. Half of the buildings count for the residential sector of witch domestic hot water heating represents 30% of the total energy use. Two typical principles for hot tap water preparation were analyzed: direct preparation using heat exchangers and using storage tanks for accumulation of domestic hot water. The aim of the study is to investigate the need of a storage tank in district heating systems by analyzing the DHW demand distribution throughout the day. Measured per capita daily DHW demand indicate a value of 45 liters compared to design norm that range from 70 to 110 liters per person and day. Measured daily distribution throughout the day has o more balanced distribution compared to design norms recommendation.